Busy Book Sebagai Media Peningkatan Motivasi dan Pengetahuan Kesehatan Gigi Mulut Bagi Anak Usia 6-7 Tahun - Sitanaya, Rini; Lesmana, Hans; Irayani Yunus, Surya; Andini, Nugi (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2024)
Children aged 6-7 years are vulnerable to oral dental disease. This is because children's knowledge and motor skills are still limited so they are not yet able to carry out oral and dental maintenance activities to the fullest. Lack of motivation in maintaining dental health contributes to the high rate of tooth decay in children of this age. Busy book is one of the media that can be made by yourself so that in addition to increasing children's knowledge about dental health, it can also increase children's creativity. Its attractive appearance makes children feel happy to learn it and easy to understand. The purpose of this study was to determine the effectiveness of providing oral health knowledge through Busy Book media in children aged 6-7 years. This research is an experimental quantitative research with a quasy experimental approach, involving 18 grade 1 students at SD 69 Mattirowali, Wajo Regency. Data from this study were analyzed using the Wilcoxon test to see the effect of using Busy Book media on increasing student knowledge. The results showed an increase in students' knowledge after gaining knowledge through Busy Book play activities. The conclusion of this study is that the use of Busy Book media is effective in increasing motivation and knowledge about oral health in children aged 6-7 years.